Digitalisasi Layanan Kesehatan Desa Grujugan Melalui Pengembangan E-Posyandu menggunakan Metode SDLC-Waterfall - Haidar Fadhila Fiqa; Rendi Putra Pradana; Mochammad Hanif; Rio Ghaniy Septiansyah (Journal of INISTA, 2022)
Posyandu is a basic health activity organized from, by and for the community assisted by health workers in an effort to improve the health quality of each village. Posyandu is a community-based health effort. Health information is generated from all routine programs carried out by the village posyandu. In managing the data, the information obtained is the main problem faced by the Posyandu in Grujugan Village. Limited access to information also causes villagers to be unable to control the health of their families, starting from children, mothers and the elderly. In an effort to improve the quality of information on examination results, a web-based posyandu information system called eposyandu was designed. The eposyandu application is built using the SDLC (System Develop Life Cycle) method with a waterfall model which is quite effective in software development. The results of the tests carried out on the application by the cadres showed results that were in accordance with the needs analysis and program design. The use of the eposyandu application is expected to improve the quality of the Posyandu information system in Grujugan Village.